2020
DOI: 10.2147/cmar.s231709
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-802 Suppresses Colorectal Cancer Cell Viability, Migration and Invasion by Targeting RAN</p>

Abstract: Purpose: Colorectal cancer is one of the most malignant tumors in the world, and the incidence is increasing every year. MicroRNAs (miRNA) are small non-coding RNAs that are involved in a variety of physiological or pathological processes. Abnormal expression of microRNA-802 (miR-802) has been demonstrated in various types of cancer. However, the expression and biological role of miR-802 in human colorectal cancer remain largely unknown. Methods: Here, we used quantitative real-time PCR (qRT-PCR) to measure mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“… 43 Small GTPase Ran was a carcinogenic protein. Several miRNAs, including miR-802, miR-2, miR-197, miR-203 could directly bind to Ran to modulate cancer cell behaviors in cancers, 15 , 44–47 which indicated that Ran involved in the regulation of malignant behaviors in cancers. Until now, some articles have revealed the regulatory mechanism of Ran in ovarian cancer, including stem-like properties, 48 cell invasion, 49 cell survival, 50 and prognosis, 13 which further indicated the carcinogenic role of Ran in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Small GTPase Ran was a carcinogenic protein. Several miRNAs, including miR-802, miR-2, miR-197, miR-203 could directly bind to Ran to modulate cancer cell behaviors in cancers, 15 , 44–47 which indicated that Ran involved in the regulation of malignant behaviors in cancers. Until now, some articles have revealed the regulatory mechanism of Ran in ovarian cancer, including stem-like properties, 48 cell invasion, 49 cell survival, 50 and prognosis, 13 which further indicated the carcinogenic role of Ran in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with the recent published study conducted by Wang et al, which showed that the low expression of miR-802 in CRC tissues was related to shorter patient's OS. 25 Together, these data suggest that miR-802 acts as tumor suppressor in CRC. The UBN2 protein is encoded by the UBN2 gene that is located on chromosome 7q34, 26 which belongs to the ubinuclein family and widely exists in human adult and fetal tissues.…”
Section: Discussionmentioning
confidence: 87%
“…In vitro experiments also further showed that miR-802 promoted the proliferation of lung cancer cells. 35 The abnormal expression of miR-802 has been confirmed in the tumor tissues or tumor cells of 15 cancers, including TSCC, 4 OSCC, 5,6 LSCC, 8 GC, [9][10][11] CRC, [12][13][14] PC, [30][31][32] HCC, [22][23][24][25] PCa, 2,33 bladder urothelial cancer, 26 BC, 15,16 CC, [17][18][19] EOC, 20 lung cancer, [34][35][36] osteosarcoma, 27,28 and melanoma. 21 To note, the abnormal expression of miR-802 in ESCC 7 and cholesteatoma 29 has only been confirmed in tumor cells.…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
“…Subsequent experiments further revealed that miR-802 expression can regulate a series of cell behaviors, including cell proliferatio n, 2,[7][8][9]11,[13][14][15]18,[20][21][22][24][25][26]28,29,31,[33][34][35] invasion, 4,6,[11][12][13][14]17,[19][20][21]33,34,36 metastasis, 2,6,7,[11][12][13][14]17,20,21,25,26,33,34,36 apoptosis, [8][9][10]13,...…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
See 1 more Smart Citation